Fabrication of Thermoplastic Elastomers (TPE) by Using Emulsion Method as an Alternative Material For Vehicle Bumper Protector - Puteri Kusuma Wardhani; Nur Padmi T; Subriyer Nasir; Puteri Kusuma Wardhani (Science and Technology Indonesia, 2018)
Research on Fabrication of Thermoplastic Elastomers (TPE) by Using Emulsion Method as an Alternative Material For Vehicle Bumper Protector aims to produce of the thermoplastic elastomers by emulsion method with variation of composition ratio of polypropylene grafting and Maleic Anhydride (PP-g-MA)(mL) : latex (mL) : glycerin, to have strong tensile strength results according to British Plastic Federation standard 0.5 – 2.4 (N/mm2) standard for bumper material elongation maximum of 22.62%. Emulsion method was used as sample preparation which is grafting polypropylene (PP) with Maleate Anhydride (MA) then continued with PP-g-MA Emulsion Making and Natural Rubber Latex Density. The observation technique of the test is done by FTIR PP-g-MA analysis, stability test, TPE visual analysis, TPE surface morphology using Scanning Electron Microscopy (SEM) tool and TPE tensile strength test. The results of FTIR analysis is that the samples closest to the carbonyl value of C = O with the highest absorption were without glycerine samples 1703.48 cm-1 with the absorption of 94.84% and carbonyl C-O 1219 cm-1 with the absorption of 95.19%. The stability testing of density values reaches the standard of the Plastic Federation of 0.91 - 1.30 g/mL, for samples having the highest and stable density values up to the seventh day of observation is a sample of PP-g-MA: Latex (75:25) which is 1.059 g/mL. In the SEM test on the PP-g-MA sample: Latex (75:25) with a average diameter pores size of 1.408 μm and the smallest diameter pore size of 0.728 μm. The highest value of tensile strength occurred in the sample with the comparison of PP-g-MA: Latex (75:25) 1,175 N/mm2 and a maximum elongation of 22.62%.